Petrochemical character of the syenitic rocks from the Yamato Mountains, East Antarctica - Shiraishi, Kazuyuki; Asami, Masao; Kanaya, Hiroshi (1983)
P(論文) Syenitic rocks occupying an area of at least 400(km)^2 in the Yamato Mountains, East Antarctica, are classified into three major types on the basis of the field occurrence and petrography; two-pyroxene syenite, clinopyroxene quartz monzo-syenite and clinopyroxene syenite. Major and trace elements Rb, Sr, Zr, Th and U are presented to reveal the petrochemical features of the syenitic rocks. The two-pyroxene syenite which has a charnockitic appearance is the earlier member among the syenitic rocks. The spacial relation between the clinopyroxene quartz monzo-syenite and the clinopyroxene syenite is not observed. All the syenitic rocks show roughly smooth trends in the major elements variation diagrams, but they overlap extensively with increasing SiO_2. The Rb, Th and U contents of the syenitic rocks are similar to those of the average crust, and Sr and Zr are much more enriched than the ordinary granitic rocks. The wide range of SiO_2 in the clinopyroxene quartz monzo-syenite and higher Rb/Sr and K/Rb ratios in the two-pyroxene syenite than the former might not prove the formation of the clinopyroxene quartz monzo-syenite from the two-pyroxene syenite by magmatic differentiation. On the other hand, it is possible that the clinopyroxene quartz monzo-syenite and the clinopyroxene syenite may be genetically related judging from their petrochemical similarity. departmental bulletin paper